Change in the relative occupational status of indigenous workers, 1986-91 - Taylor, John, 1953-; Liu, Jin.; Australian National University. Centre for Aboriginal Economic Policy Research (Canberra : Centre for Aboriginal Economic Policy Research, Australian NAtional University, 1996)
Discusses whether Indigenous employment strategies implemented during the later period of the 1980s and early 1990s coincided with a rise in employment status against similar employment strategies in the general population; analyses data from the 1986 and 1991 Censuses, and demographic categories.
Bibliography: p. 23.
Keywords: Vocational education -- Australia -- Statistics; Aboriginal Australians -- Employment -- Statistics; Occupations -- Australia -- Statistics; Women -- Vocational education -- Australia; Occupational training for minorities -- Australia; Women, Aboriginal Australian -- Employment -- Statistics; Employment - Labour market; Education - Vocational and trades